New insights into antiphospholipid-related endothelial dysfunction by assessment of vascular glycocalyx layer: results from a preliminary cross-sectional study. (February 2020) - Miranda, S; Billoir, P; Le Besnerais, M; Joannides, R; Richard, V; Lévesque, H; Armengol, G; Bellien, J; Benhamou, Y
Introduction: Antiphospholipid syndrome (APS) is associated with greater atherothrombotic risk and endothelial dysfunction, suggesting that endothelial glycocalyx is impaired in this disease. Objectives: The aim was to investigate the endothelial glycocalyx and the relationship between glycocalyx markers, endothelial dysfunction parameters and atherosclerotic markers in APS. Methods: A total of 15 primary arterial APS patients and healthy controls were included in the study. Glycocalyx was assessed in both groups by sublingual sidestream dark field imaging and syndecan-1 plasma level. Endothelial function was evaluated by brachial artery flow-mediated dilatation (FMD) and early atherosclerosis by carotid intima media thickness (IMT). Thrombotic profile was also performed by measuring the plasma level of the tissue factor (TF). Results: APS patients had significantly increased syndecan-1 plasma level 38.6 ± 5.0 pg/ml vs. 19.1 ± 3.5 pg/ml; p  < 0.01 and a reduced glycocalyx thickness 0.26 ± 0.03 µm vs. 0.75 ± 0.07 µm; p  < 0.01 compared with control. FMD was impaired in APS patients compared with control, 5.68% ± 0.42 vs. 8.29 ± 0.30, p  < 0.01, respectively. IMT was significantly increased in APS patients compared with control, 0.52 ± 0.13 mm vs. 0.40 ± 0.06 mm, p  < 0.01, respectively. Soluble TF, thiobarbituric acid-reactive substances levels were increased in the sera from APS patients compared with control. Conclusions: This preliminary study supports, for the first time, that in APS patients endothelial glycocalyx is impaired, which could lead to thrombosis, endothelial dysfunction and early atherosclerosis.